Perencanaan Strategik Dalam Peningkatan Mutu Pendidikan Madrasah Tsanawiyah Negeri 1 Padangsidimpuan - Pane, Daud; Zulhamri (Sekolah Tinggi Ilmu Tarbiyah Padang Lawas (STIT PL) Gunung Tua, 2024)
This study aims to determine how strategic planning in improving the quality of education in Madrasah Tsanawiyah Negeri 1 Padangsidimpuan. This research uses qualitative research. This is based on knowing the importance of strategic planning in improving the quality of education in Madrasahs. Qualitative research is a research procedure that produces descriptive data in the form of written or spoken words from people whose behavior can be understood. The subject of this research is directed at finding data from the Principal of Madrasah Tsanawiyah Negeri 1 Padangsidimpuan, Head of Administration, Student Affairs. The research data collection was obtained by using interview, observation, and documentation studies. While the findings in this study are the strategic planning process in improving the quality of education at Madrasah Tsanawiyah Negeri 1 Padangsidimpuan goes well with the implementation of all the strategic plans that have been provided by the institution. So that the students and students are arranged in a rapid and structured manner by following the rules that are applied to both the teacher, staff and students. Improving the quality of education can be seen clearly from the achievements they have achieved and the goals of their education have been achieved.